(untitled) (Global Journal of Management and Business Research, 2023)
The study investigated the effect of capital structure on financial performance of manufacturing firms that are listed at the Nairobi Securities Exchange. The population of the study consisted of 8 manufacturing and allied firms. The period of study was over 8 years (eightyears) period from 2013 and 2020. The study used secondary data. Multilinear regression model was used to assess the financial performance of these manufacturing firms that are quoted at NSE. Both descriptive statistics and Pearson correlation matrix was used to assess the outcome of the study. The following results were found: A unit increase in the debt in the firm capital structure results in a -0.782 decrease in the financial performance of the manufacturing firms while an increase in one unit of equity results in 0.667 increase in financial performance of the firms. There was negative correlation between the debt ratio and the financial performance and a positive correlation between equity and financial performance of manufacturing firms. The study also showed that firm’s liquidity level has a positive influence on the financial performance, which indicates that, the more liquid a firm is in meeting its short term obligations the more profitable it becomes.